High Content Screening in NHBE cells shows significantly reduced biological activity of flavoured e-liquids, when compared to cigarette smoke condensate. (August 2019) - Czekala, Lukasz; Simms, Liam; Stevenson, Matthew; Trelles-Sticken, Edgar; Walker, Paul; Walele, Tanvir
Abstract: There is scientific agreement that the detrimental effects of cigarettes are produced by the formation of Harmful and Potentially Harmful Constituents from tobacco combustion and not by nicotine. For this reason numerous public health bodies and governments worldwide have indicated that e-cigarettes have a central role to play in tobacco harm reduction. In this study, high content screening (HCS) was used to compare the effects of neat e-liquids and 3R4F reference cigarette smoke condensate (CSC), which served as a positive control, in Normal Human Bronchial Epithelial (NHBE) cells. The endpoints measured covered cellular health, energy production and oxidative stress. Base liquids, with or without nicotine, and commercial, flavoured, nicotine-containing e-liquids (CFs), had little or no effect on cell viability and most HCS endpoints even at significantly higher concentrations (typically 100 times or higher) than 3R4F CSC. CSC induced a dose-dependent decrease of cell viability and triggered the response in all HCS endpoints. Effects of CFs were typically observed at or above 1%. CF Menthol was the most active flavour, with minimum effective concentrations 43 to 659 times higher than corresponding 3R4F CSC concentrations. Our results show a lower biological activity of e-liquids compared to cigarette smoke condensate in this experimental setting, across wide range of cellular endpoints. Highlights: High Content Screening was used to assess a selection of e-liquids. Endpoints included Cellular Health, Energy production and oxidative stress. Cigarette smoke condensate induced effects in all endpoints from 0.001% concentration. E-Liquids were active at concentrations 100 times higher than those for cigarette condensate. Flavours play a critical role in attracting, and retaining smokers to e-cigarettes